2010
DOI: 10.1111/j.1365-2958.2010.07053.x
|View full text |Cite
|
Sign up to set email alerts
|

Phosphorylation of phosducin‐like protein BDM‐1 by protein kinase 2 (CK2) is required for virulence and Gβ subunit stability in the fungal plant pathogen Cryphonectria parasitica

Abstract: Phosducin-like proteins are conserved regulatory components of G-protein signalling pathways, which mediate many physiological processes. Identified throughout eukaryotic genomes, they are thought to serve as regulators of Gβγ assembly. Cryphonectria parasitica, a plant pathogen and causative agent of chestnut blight, contains three Gα, one Gβ, one Gγ subunits and phosducin-like protein BDM-1 that have important roles in pigmentation, sporulation and virulence. Deletion of either Gβ subunit or BDM-1 produces i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
11
0

Year Published

2010
2010
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 17 publications
(14 citation statements)
references
References 45 publications
(109 reference statements)
1
11
0
Order By: Relevance
“…Similar results were obtained in Cryphonectria parasitica, a pathogenic fungus that is the main cause of chestnut blight, where Gb stability was found to be dependent on the presence of beta disruption mimic factor-1 (a PhLP1 homolog) and its phosphorylation by CK2 (Salamon et al, 2010). Another study confirmed the finding that Gb interacts with the CCT complex in the absence of Gg, and that Gg competed with CCT for binding to Gb (Wells et al, 2006).…”
supporting
confidence: 75%
“…Similar results were obtained in Cryphonectria parasitica, a pathogenic fungus that is the main cause of chestnut blight, where Gb stability was found to be dependent on the presence of beta disruption mimic factor-1 (a PhLP1 homolog) and its phosphorylation by CK2 (Salamon et al, 2010). Another study confirmed the finding that Gb interacts with the CCT complex in the absence of Gg, and that Gg competed with CCT for binding to Gb (Wells et al, 2006).…”
supporting
confidence: 75%
“…A number of other virulence factors have been identified in C. parasitica using specific gene mutations. These factors include G‐protein signalling (Gao and Nuss, ), a kexin‐like protease involved in protein secretion (Jacob‐Wilk et al ., ), an Ste12 transcription factor homologue (Deng et al ., ), a tannic acid‐inducible laccase (Chung et al ., ), a cyclophilin (Chen et al ., ), protein kinase 2 (CK2)‐mediated signalling (Salamon et al ., ) and an inhibitor (CpBir1) of apoptosis proteins (Gao et al ., ). The availability of the genome sequence of C. parasitica (http://genome.jgi.doe.gov/Crypa2/Crypa2.home.html) will probably benefit research on the mechanisms underlying its pathogenesis.…”
Section: Infection Process and Virulence Factorsmentioning
confidence: 99%
“…On the other hand, casein kinase II (CK2) activity mediates signal responsible for virulence in a fungal plant pathogen, Cryphonectria parasitica in which the elimination of CK2 phosphorylation site lead to a lack of virulence (Salamon et al, 2010). Apart from that, glycosylation regulates how proteins fold, their biological activity as well as their half-life (Kotz et al, 2010).…”
Section: Discussionmentioning
confidence: 99%